Not so FAST—let’s not abandon the pediatric focused assessment with sonography in trauma yet - Moore, Chris; Liu, Rachel (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
The recent article by Holmes et al. (1) represents the largest prospective trial of the focused assessment with sonography in trauma (FAST) in stable pediatric trauma patients. The nal conclusion of the authors is that the “ ndings do not support the routine use of the FAST in this setting.” Based on their data and stated outcomes this is not an untrue statement, but before we put away the ultrasound machine on these patients some additional perspective may be warranted.